2017
DOI: 10.15208/beh.2017.12
|View full text |Cite
|
Sign up to set email alerts
|

Do tax incentives matter for investment? A literature review

Abstract: Abstract:The effectiveness of tax incentives in attracting FDI remains one of the unsettled concepts in public finance. The importance of tax incentives in attraction of internationally mobile capital differs with the jurisdiction of the study and the methodology used in drawing conclusions. This study in reviewing both theoretical and empirical literature seeks to establish the merits and demerits of tax incentives. This is because though they receive a lot of criticism tax incentives continue to be used in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 38 publications
1
23
0
1
Order By: Relevance
“…Scientists [6] researching the use of tax incentives in developing countries prove that infrastructure, human capital and institutions have a large impact on attracting investment compared to tax incentives. Similar conclusions were formulated in an article by South African authors [7] who believe that despite the important role in attracting investments played by tax incentives, they are effective for attracting any significant investments only in combination with non-tax measures, especially if availability of developed infrastructure.…”
Section: Proceedings Of the Russian Conference On Digital Economy Andsupporting
confidence: 73%
“…Scientists [6] researching the use of tax incentives in developing countries prove that infrastructure, human capital and institutions have a large impact on attracting investment compared to tax incentives. Similar conclusions were formulated in an article by South African authors [7] who believe that despite the important role in attracting investments played by tax incentives, they are effective for attracting any significant investments only in combination with non-tax measures, especially if availability of developed infrastructure.…”
Section: Proceedings Of the Russian Conference On Digital Economy Andsupporting
confidence: 73%
“…As indicated by Havránek and Iršová (2010), the governments of host countries often use investment incentives as a tool addressed to foreign investors in order to compensate for shortcomings such as the existence of a high burden of employment costs and/or insufficient labor productivity in the host country. In a similar sense, a review study by Munongo et al (2017) concluded that most of the empirical studies that they had explored suggested a combination of incentives with other factors such as macroeconomic conditions, infrastructure, and transparent institutions in an effort to effectively attract FDI. Similarly, a meta-analytic review by Bailey (2018) concluded that "good government" attracts FDI.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Absence of tax sparing provisions in bilateral tax treaties can cause nullification of host country tax incentives by home country taxation. In addition, Munongo et al (2017) pointed to other problems associated with tax incentives such as difficulties associated with the administration of tax incentives, misallocation of resources, and potential corruption, as a result of which they may be unattractive to investors.…”
Section: Slovakiamentioning
confidence: 99%
“…A study was conducted on tax incentives and investment to review both theoretical and empirical literatures to establish the merits and demerits of tax incentives (Munongo, Akanbi, & Robinson, 2017).They found that, most of the empirical studies have been explored are concluded that though tax incentives might be important in attracting FDI they are more effective when combined with other non-tax factors.…”
Section: Literature Reviewmentioning
confidence: 99%